Diagnostic Value of Myeloperoxidase Index in Bacterial Infections - Mirna Rahmafindari; Paulus Budiono Notopuro; Betty Agustina Tambunan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Infectious diseases remain a serious problem in Indonesia. Myeloperoxidase (MPO) is a substance released by neutrophils, which activates the synthesis of hypochlorous acid (HOCL) from hydrogen peroxide (H2O2) and chloride ion (Cl-). Hypochlorous acid plays a vital role in the body's defense against infection. Myeloperoxidase Index (MPXI) is a parameter in the hematology analyzer Advia 2120i based on the principle of flow cytometry. This study aimed to determine the diagnostic value of MPXI in patients with bacterial infections. The study was a cross-sectional observational analysis. The samples consisted of a group of patients with bacterial infection and a group of healthy subjects. The specimens used in this study were whole blood + anticoagulant (EDTA) in a purple tube with a volume of 3 mL to determine the MPXI value in both groups using ADVIA 2120i hematology analyzer. The study subjects consisted of a group of patients with bacterial infections (69 patients) and a group of healthy subjects (33 people). Analysis of the MPXI ROC curve with a cut-off ≥ -5.8 and < -5.8, showed AUC of 0.323 (CI=95%, p=0.004), sensitivity of 34.8%, specificity of 39.4%, Positive Predictive Value (PPV) of 54.5%, and Negative Predictive Value (NPV) of 22.4%. Due to its low diagnostic value, the MPXI value was not recommended to be used as a diagnostic instrument for bacterial infections. Also, further research was highly needed.